The role of inflammation and innate immune cells in young myocardial infarction patients without traditional risk factors. (3rd October 2022) - Mol, J H Q; Van Tuijl, J; Bekkering, S; Stolk-Van Der Heijden, C; Damen, S; Cossins, B; Van Emst, L; Pop, G; Netea, M; Van Royen, N; Riksen, N; El Messaoudi, S
Abstract: Background: There is a group of patients that develops myocardial infarction (MI) in the absence of standard modifiable risk factors (SMuRFs) and at a young age. Identifying the mechanism underlying the development of atherosclerosis in these patients is paramount in order to develop adequate treatment strategies. Atherosclerosis is characterized as an inflammatory disease in which monocytes play a pivotal role. Circulating monocytes of atherosclerosis patients with SMuRFs have a pro-inflammatory phenotype. At present, the contribution of systemic inflammation, or innate immune cell activation in particular, in young SMuRFless MI patients is unknown. Purpose: The aim of this study was to characterize the inflammatory profile of young SMuRFless MI patients, with an in-depth focus on monocyte phenotype, function and their epigenetic profiles. Methods: We recruited 20 SMuRFless patients who suffered from a recent (1–4 year ago) MI and were <50 years old at the time. These patients were age- and sex matched to 18 healthy controls, who did not have atherosclerosis, as determined by coronary CT-scan. Blood samples were obtained after evening out any potential immunomodulating effect of statins and aspirin by interrupting statins for two weeks in patients and starting aspirin therapy for two weeks in controls. In both groups we studied circulating inflammatory markers with proximity extension assay, circulating monocyte (subset) phenotype with flow cytometry, and cytokine production of isolated peripheral blood mononuclear cells (PBMC) after stimulation with Toll-Like Receptor-agonists. Histone marks of chromatin accessibility were assessed on the promotor regions of several inflammatory cytokines in unstimulated isolated monocytes by chromatin immunoprecipitation (ChIP). Results: PBMCs from patients showed elevated cytokine production after ex vivo stimulation compared to controls (P=0.046) (Figure 1). ChIP analysis of unstimulated monocytes revealed an overall enrichment of transcriptionally permissive tri-methylation of lysine 4 on histone H3 (H3K4me3) on the promoter regions of cytokines in patients compared to controls (Figure 2). Levels of H3K4me3 on IL-10 were significantly higher in patients (p=0.04). For TNF-α and IL-6 H3K4me3 levels did not reach statistical significance (p=0.07 and p=0.13 respectively). Despite the functional hyperresponsiveness, no differences were seen in monocyte phenotype on flow cytometry analysis (not shown). Additionally there were no differences in circulating high-sensitive C-reactive protein or other circulating inflammatory markers (not shown). Conclusions: Circulating monocytes in SMuRFless MI patients are characterized by pro-inflammatory behavior, which is mediated by transcriptionally permissive epigenetic modifications at the promoters of key inflammatory cytokine genes. These findings are present in the absence of active systemic inflammation. Funding Acknowledgement: Type of funding sources: None.